Simulation of active control using fuzzy logic applied to a pulse combustor - Botura, C. A. [UNESP]; Botura, G. [UNESP]; Carvalho, J. A.; Mesquita, L. [UNESP] (FapUNIFESP (SciELO), 2002)
This work analyzes an active fuzzy logic control system in a Rijke type pulse combustor. During the system development, a study of the existing types of control for pulse combustion was carried out and a simulation model was implemented to be used with the package Matlab and Simulink. Blocks which were not available in the simulator library were developed. A fuzzy controller was developed and its membership functions and inference rules were established. The obtained simulation showed that fuzzy logic is viable in the control of combustion instabilities. The obtained results indicated that the control system responded to pulses in an efficient and desirable way. It was verified that the system needed approximately 0.2 s to increase the tube internal pressure from 30 to 90 mbar, with an assumed total delay of 2 ms. The effects of delay variation were studied. Convergence was always obtained and general performance was not affected by the delay. The controller sends a pressure signal in phase with the Rijke tube internal pressure signal, through the speakers, when an increase the oscillations pressure amplitude is desired. On the other hand, when a decrease of the tube internal pressure amplitude is desired, the controller sends a signal 180° out of phase.
Keywords: Fuzzy logic; Pulse combustion; Rijke tubes; Combustion; Combustors; Computer simulation; Fuzzy control; Membership functions; Inference rule; Oscillation pressure amplitude; Rijke type pulse combustor; Tube internal pressure; Tube internal pressure amplitude; Fuzzy sets